How do people reason in dynamic games? - Nadine Chlaß; Andrés Perea (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Do individuals choose how to a solve a dynamic game or is their mode of reasoning a type-like predisposition? We show experimentally that an individual's propensity to forwardly or backwardly induct is a function of (i) her belief whether an opponent's previous action was a trembling hand mistake or a rational choice, and (ii) her personality. In a two-stage game, the individual observes an action of a computerized opponent (stage 1) before both interact (stage 2). The opponent chooses rationally most of the time and makes random choices with a small commonly known likelihood. Hence, the opponent's action in stage 1 discloses with some probability the opponent's type (choice) in stage 2. The individual can either believe that (i) the opponent chose randomly in stage 1, or that (ii) the opponent made a rational choice. An individual rationally responds to this belief if she solves stage 2 by backwards induction in the first, and by forward induction in the second case.
Keywords: C73; C91; D82; 330